Efektivitas layanan bimbingan kelompok dengan menggunakan teknik sosiodrama untuk meningkatkan perilaku prososial peserta didik - Nurmaliza, Nurmaliza; Syukur, Yarmis (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
This research is based on the problem of low prosocial behavior of students. It is argued that students are more individualistic and self-centered than friends around them. The efforts made in improvingthe prosocial behavior of students are with group guidance services using sociodrama techniques. The purpose of this study was to look at the effectiveness of group guidance services to improve the prosocial behavior of learners. The research method used is quantitative which uses Quasi Edesign with pre-test and post-test control group design. The sample in this study was MTsN 2 Padang City students totaling 16 students with high, medium and low prosocial behavior categories. The instrument used in this study is a prosocial behavior instrument with a likert scale. The sampling technique is used by purposive sampling. Data were analyzed using the Wilcoxon Signed Ranks Test and the Kolmogrof Smirnov 2 Independent Sample test with the help of SPSS version 2.0. The results of this study show that group guidance services using sociodrama techniques are effective in improving the prosocial behavior of students. The results of this study can be used as a reference in helping guidance and counseling service programs, especially using group guidance services with sociodrama techniques to improve the prosocial behavior of students.